Leisure experiences in socio-educational organizations of people with disabilities and their contribution to the SDG - Ruiz-Calzado, Inmaculada (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
The objective of this study has been to evaluate the quality of leisure and free time activities specifically aimed at people with physical, mental and/or sensory disabilities through a socio-educational organization in the city of Córdoba (Spain). The methodology used was quantitative. It was a case study carried out in a socio-educational organization that cares for people with disabilities. The instrument used was the Scale for the assessment of leisure and free time activities (Hernández, 2001) completed by 67 participants. The most interesting results showed relationships with the age variable. However, no differences were found between groups for the rest of the study variables.